Specific habitat requirements and niche conservatism for nine species of the Mexican genus Thelocactus (Cactaceae) - Alessandro Mosco (Revista Mexicana de Biodiversidad)
Although Mexican Cactaceae are a significative component of Mexican flora and have a relevant economic and ornamental value, the knowledge of the environmental factors characterizing their niche is still rather limited. This study was aimed at defining the ecological niche and potential distribution of 9 species of the genus Thelocactus. Climatic and topographic variables constraining the distribution of Thelocactus species were identified by means of environmental niche models (ENM) and ordination techniques and used to generate potential distribution maps. The constructed ENMs were compared to assess the similarities of the ecological niche of Thelocactus species and to know if they share the same ecological niche space. The distribution of Thelocactus species was mostly limited by isothermality and precipitation of wettest quarter. The differences in habitat requirements were well documented by the significative differences in the niche ecological space as shown by the equivalency test, while the high percentage of niches that were more similar than expected by chance suggest a high degree of niche conservatism among Thelocactus species. The spatial predictions could serve to improve field design sampling to discover new populations, while niche characteristics could be relevant for improving preservation actions and guiding reintroduction programs for a better conservation of Thelocactus species.